Physical Activity and Sedentary Behavior on Bone Health in Adults: A Systematic Review - da Costa, Julio Cesar (2024)
The objective was to analyze the longitudinal associations of physical activity (PA) and Sedentary behavior (SB) on bone health indicators (BHI) in healthy young adults. Articles were selected from five databases and 17 longitudinal studies were selected after meeting the inclusion and exclusion criteria. Among these, only one study assessed the association between childhood PA and adult BHI, the results showed no significant association between PA and BHI. Positive associations between adolescence and adulthood were observed between PA with bone mineral content and density and bone microarchitecture. In adulthood, the results were divergent; among the three studies located, two found a positive association. SB was negatively associated with bone mineral density and content from childhood to adulthood. However, from adolescence to adulthood, it was negatively associated with total tibia area but positively associated with trabecular thickness, cortical thickness, and cortical bone mineral. The evidence of the positive effect of PA and its intensities between adolescence and adulthood on BHI seems to be more consolidated, and it is still necessary to understand the role of intensities, volume of PA and SB in different periods of life with BHI in adulthood.